Capillary cooling technology with forced-air cross ventilation: an eco-friendly onion storage technology - Gulandaz, Md Ashrafuzzaman; Brahma , Shyamal; Haque , Muhammad Arshadul; Amin, Md Nurul (Revista Brasileira de Engenharia de Biossistemas, 2026)
The objective of this study was to develop a solar-powered forced air-ventilated onion storage system (FAVS) with capillary cooling technology and to compare the effectiveness of the system with other common onion storage practices. Onion is one of the economically important crops that suffer significant postharvest losses due to inadequate storage conditions. A FAVS unit (2300×1200×3400 mm) with a 3000 kg total capacity (1000 kg/layer) was designed and fabricated and compared with three conventional methods such as Traditional Storage (TDS), Net Sack Storage (SNS), and Jute Sack Storage (SJS). BARI Piaj-4 was kept in bulk condition for 120 days, and data of physiological weight loss (PWL), decay percentage, moisture content, total soluble solids (TSS), firmness, and fungal infection were measured at 30-day intervals. A 130-watt solar panel charges a battery that runs ten 6-watt exhaust fans all day. Side exhaust fans intake fresh air from outside to remove surface moisture from the onion as capillary action, while the exhaust fan on top sucks hot air from the FAVS system. The FAVS system outperformed, with the lowest decay (4.43%) and fungal infection (4.33%) compared to TDS (8.12% and 8.10%), SNS (8.80% and 8.90%), and SJS (9.27% and 9.37%). FAVS maintained the highest and most stable moisture content (75.37%), while physiological weight loss remained below 4%, which is significantly less than traditional methods (9%). Furthermore, the system showed minimum reductions in firmness (0.32%) and TSS (1.37%), indicating better quality storage. The findings support the adoption of FAVS as an effective and environmentally friendly alternative to traditional onion storage practices.